The owl, the raven & the dove : the religious meaning of the Grimms' magic fairy tales - Murphy, G. Ronald, 1938- (OUP E-Books., 2000)
This study takes five of the Grimm brothers' best-known tales and argues that the Grimms saw them as Christian fables. The author examines the arguments of previous interpreters of the tales, and demonstrates how they missed the Grimms' intention.